(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: The determine the functional outcome of custom-built fixed hinged prosthesis for tumors around the knee. Methods: This descriptive study was conducted in Department of Orthopedics & Spine Surgery Ghurki Trust Teaching Hospital Lahore from 3rd January 2015 to 3rd January 2021.All adults patients of either gender and age with tumours of distal femur,proximal tibia or both fulfilling the inclusion criteria were operated for custom-built fixed hinged prosthesis.Post operative functional outcome was determined using Musculoskeletal Tumor Society(MSTS) system and results were graded as excellent(75-100%), moderate (70-74%), Good (60-69%), Fair(50-59%) and Poor (<50%) outcome.Functional outcome was compared for type of tumor,gender and site of tumour and P value calculated with simple Pearson Chi-Square test.P value<0.05 was considered significant. Results: A total of 34 patients were included in our study.The mean age was 30.65±14.23 years.Male patients were 23(67.6%) and female 11(32.4%). Osteosarcoma was present in 25(73.5%) patients,Giant cell tumour in 5(14.7%) and Ewing Sarcoma in 4(11.8%). Tumor involvement of the distal femur was present in 25(73.5%), proximal tibia in 7(20.6%) and both femur and tibia in 2(5.9%) patients. The mean Musculoskeletal Tumor Society(MSTS) score at 2.5 years was 73%(range 34% to 95%).Excellent functional outcome was noted in 22(64.7%), moderate in 2(5.9%),good in 7(20.6%), fair in 1(2.9%) and poor in 1(2.5%). No significant difference was noted when functional outcome was compared for gender,type of tumour,stage of tumor,location of tumor, side of tumor and type of stem fixation (P>0.05). Conclusion: Custom-built fixed hinge prosthesis for tumors around the knee yielded excellent functional results in majority of our patients. We found custom build fixed hinged endoprosthetic reconstruction safe and effective technique for limb salvage in cases of distal femur and proximal tibia tumors.